2014
DOI: 10.1097/ana.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research Into Anesthetic Neurotoxicity

Abstract: General anesthetics mitigate distress and exaggerated hemodynamic responses to pain and stressful stimulation, allowing surgery and diagnostic procedures to be performed worldwide in millions of children every year. Emerging studies, mainly carried out in early postnatal laboratory animals, demonstrate widespread neuronal elimination, alteration in neuronal circuitry, and long-term neurological disabilities following exposure to all commonly used sedatives and anesthetics. These findings have raised concerns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous cohort studies have found mixed results. 19 Some studies have found an association between exposure to anaesthesia in early childhood and increased risk of poor neurodevelopmental outcome. 16 18 , 20 24 , 28 Although this association fits with preclinical animal data, it may also be explained by the confounding effects of surgery, pathology or co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cohort studies have found mixed results. 19 Some studies have found an association between exposure to anaesthesia in early childhood and increased risk of poor neurodevelopmental outcome. 16 18 , 20 24 , 28 Although this association fits with preclinical animal data, it may also be explained by the confounding effects of surgery, pathology or co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reviews that have concluded that there is an association between anaesthesia in childhood and neurodevelopmental outcome. 19 , 31 There have been two meta-analyses that have found evidence for an association between anaesthesia in children and a range of neurodevelopmental outcomes. 16 , 30 All reviews and meta-analyses acknowledge the weaknesses of the cohort studies; including strong likelihood of confounding, bias, heterogeneous populations at times of exposure, and heterogeneous outcome measures, some of which are poorly defined or insensitive.…”
Section: Research In Contextmentioning
confidence: 99%
“…The individual and societal costs of management of these problems are substantial (Young and Inouye, 2007 ; Dasgupta and Hillier, 2010 ) and the health care costs soar into the billions of dollars annually (Leslie et al, 2008 ). POD has been conceptualized as a “disease of the elderly” because of its high prevalence in late life and that older adults with dementing disorders and/or vascular compromise are particularly prone to the risks of POD (Beals et al, 2003 ; Olney et al, 2004 ; Baranov et al, 2009 ; Lei et al, 2014 ; Strøm et al, 2014 ; Fong et al, 2015 ). Historically, the expression of POD has hinged on the concept that anesthetic agents may be toxic to brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term learning and memory impairment has also been observed in rats following anesthetic exposure (Callaway et al, 2012 ; Lin et al, 2014 ). The literature shows growing evidence for neurotoxicity in humans, such as neuroanatomical structural alterations as well as cognitive and behavioral changes in children (Lei et al, 2014 ; Backeljauw et al, 2015 ). These behavioral changes include problems with sleep (Bakri et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%